For a quadratic equation, if one of the root is $\sqrt 2 + \sqrt 3 $, then the equation is ${x^2} - 2\sqrt 2 x - 1 = 0$.
A. True
B. False
Answer
Verified
482.7k+ views
Hint:Use Shreedharacharya formula to calculate the roots of the quadratic equation. Then check whether one of the roots is$\sqrt 2 + \sqrt 3 $.
Formula used:Shreedharacharya formula for finding roots of quadratic equation. $ x = \dfrac{{ - b \pm \sqrt D }}{{2a}} = \dfrac{{ - ( - 2\sqrt 2 ) \pm \sqrt {{{( - 2\sqrt 2 )}^2} - 4(1)( - 1)} }}{{2(1)}}$
Complete step-by-step answer:
We are given that a quadratic ${x^2} - 2\sqrt 2 x - 1 = 0$ has one of the roots $\sqrt 2 + \sqrt 3 $. We need to check whether the statement is true or not.
To find the roots of the equation we need to use the Shreedharacharya formula. We will start from understanding the Shreedharacharya formula and it’s derivation.
Let the general quadratic equation be $a{x^2} + bx + c = 0$. We have,
$a{x^2} + bx + c = 0$
Multiply both sides by 4a
$ \Rightarrow 4{a^2}{x^2} + 4abx + 4ac = 0$
Subtracting both side by 4ac
$ \Rightarrow 4{a^2}{x^2} + 4abx = - 4ac$
Adding both sides ${b^2}$ we get,
$ \Rightarrow 4{a^2}{x^2} + 4abx + {b^2} = - 4ac + {b^2}$
Completing the square on LHS we get,
$ \Rightarrow {(2ax + b)^2} = - 4ac + {b^2} = D$
Taking square roots we get,
$ \Rightarrow 2ax + b = \pm \sqrt D .$
Subtracting both sides b and dividing by 2a we get,
$ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}}.…………. (1)$
Thus roots of quadratic equation are given by $ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}}.$
Now, using the Shreedharacharya formula in ${x^2} - 2\sqrt 2 x - 1 = 0$.
$a = 1$
$b = - 2\sqrt 2 $
$c = - 1$
Putting the values of a, b and c in equation (1) we get,
\[ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}} = \dfrac{{ - ( - 2\sqrt 2 ) \pm \sqrt {{{( - 2\sqrt 2 )}^2} - 4(1)( - 1)} }}{{2(1)}}\].
Simplifying the values we get,
\[ \Rightarrow x = \dfrac{{2\sqrt 2 \pm \sqrt {8 + 4} }}{2} = \dfrac{{2\sqrt 2 \pm \sqrt {12} }}{2}\]
Calculating it further we have,
\[ \Rightarrow x = \dfrac{{2\sqrt 2 \pm 2\sqrt 3 }}{2}\]
Taking 2 common in numerator and cancelling out on the RHS we have,
\[ \Rightarrow x = \sqrt 2 \pm \sqrt 3 \]
This shows that the quadratic equation has roots $\sqrt 2 + \sqrt 3 $ and $\sqrt 2 - \sqrt 3 $.
Since, $\sqrt 2 + \sqrt 3 $ is a root of the quadratic equation ${x^2} - 2\sqrt 2 x - 1 = 0$. Therefore, the statement given is true.
So, the correct answer is “Option A”.
Note:While calculating for the roots in a quadratic equation $ax^2+bx+c=0$ we first need to find the D which is also called the discriminant i.e $D=b^2-4ac$. If this discriminant is more than zero then the roots of the equation are real.
Formula used:Shreedharacharya formula for finding roots of quadratic equation. $ x = \dfrac{{ - b \pm \sqrt D }}{{2a}} = \dfrac{{ - ( - 2\sqrt 2 ) \pm \sqrt {{{( - 2\sqrt 2 )}^2} - 4(1)( - 1)} }}{{2(1)}}$
Complete step-by-step answer:
We are given that a quadratic ${x^2} - 2\sqrt 2 x - 1 = 0$ has one of the roots $\sqrt 2 + \sqrt 3 $. We need to check whether the statement is true or not.
To find the roots of the equation we need to use the Shreedharacharya formula. We will start from understanding the Shreedharacharya formula and it’s derivation.
Let the general quadratic equation be $a{x^2} + bx + c = 0$. We have,
$a{x^2} + bx + c = 0$
Multiply both sides by 4a
$ \Rightarrow 4{a^2}{x^2} + 4abx + 4ac = 0$
Subtracting both side by 4ac
$ \Rightarrow 4{a^2}{x^2} + 4abx = - 4ac$
Adding both sides ${b^2}$ we get,
$ \Rightarrow 4{a^2}{x^2} + 4abx + {b^2} = - 4ac + {b^2}$
Completing the square on LHS we get,
$ \Rightarrow {(2ax + b)^2} = - 4ac + {b^2} = D$
Taking square roots we get,
$ \Rightarrow 2ax + b = \pm \sqrt D .$
Subtracting both sides b and dividing by 2a we get,
$ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}}.…………. (1)$
Thus roots of quadratic equation are given by $ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}}.$
Now, using the Shreedharacharya formula in ${x^2} - 2\sqrt 2 x - 1 = 0$.
$a = 1$
$b = - 2\sqrt 2 $
$c = - 1$
Putting the values of a, b and c in equation (1) we get,
\[ \Rightarrow x = \dfrac{{ - b \pm \sqrt D }}{{2a}} = \dfrac{{ - ( - 2\sqrt 2 ) \pm \sqrt {{{( - 2\sqrt 2 )}^2} - 4(1)( - 1)} }}{{2(1)}}\].
Simplifying the values we get,
\[ \Rightarrow x = \dfrac{{2\sqrt 2 \pm \sqrt {8 + 4} }}{2} = \dfrac{{2\sqrt 2 \pm \sqrt {12} }}{2}\]
Calculating it further we have,
\[ \Rightarrow x = \dfrac{{2\sqrt 2 \pm 2\sqrt 3 }}{2}\]
Taking 2 common in numerator and cancelling out on the RHS we have,
\[ \Rightarrow x = \sqrt 2 \pm \sqrt 3 \]
This shows that the quadratic equation has roots $\sqrt 2 + \sqrt 3 $ and $\sqrt 2 - \sqrt 3 $.
Since, $\sqrt 2 + \sqrt 3 $ is a root of the quadratic equation ${x^2} - 2\sqrt 2 x - 1 = 0$. Therefore, the statement given is true.
So, the correct answer is “Option A”.
Note:While calculating for the roots in a quadratic equation $ax^2+bx+c=0$ we first need to find the D which is also called the discriminant i.e $D=b^2-4ac$. If this discriminant is more than zero then the roots of the equation are real.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE